Learning Reading Comprehension Through Analyzing A Novel “I Am A Prodigy” On SFL - Edy Suseno (Prodi Pendidikan Bahasa dan Sastra Indonesia IKIP WIDYA DARMA, 2022)
Learning reading results in a disappointment for many EFL learners. They get a problem to understand the passage about. It seems that they do not have a sufficient vocabulary list and constructing sentence ability. They faced a problem in the situational and cultural contexts. The mastery of the two contexts leads students to gain a make meaning. It is a way to assist the students to understand the text and to write sentences. To help the students cope with their difficulties, analyzing a novel is promising. By analyzing the text, the students learn to build vocabulary and sentences. It is part of the situational context. This research used a novel “I am a Prodigy” as the data to be analyzed. Analyzing that kind of data is implementing cultural context. It applies the situational context into a written product. To analyze the content of the text, a rubric was applied. The postmodernist viewpoints are the categories used in the rubric. The result of the analysis was the detailed description of semantically and pragmatically to interpret the words and sentences in the text. It builds the students’ vocabulary and syntax knowledge. It means that it can build the readers’ competence in a situational context. Furthermore, in commenting on the data, it leads them to develop their cultural context. This kind of result is very beneficial for the students and teachers to enhance the teaching-learning reading process in the classroom. It also inspires the other researchers to develop it some further